Design elements typography fundamentals : a graphic style manual for understanding how typography affects design - Cullen, Kristin (Design elements, 2012)
"Explore the fundamentals of typography with this practical new guide. An instructional reader rather than historical survey, Design Elements: Typography Fundamentals uses well-founded, guiding principles to teach the language of type and how to use it capably. Designers are left with a solid ground on which to design with type. Limitless potential for meaningful and creative communication exists--this is the field guide for the journey!"--